Ameliorative effects of pine bark extract on cisplatin-induced acute kidney injury in rats. (1st January 2017) - Lee, In-Chul; Ko, Je-Won; Park, Sung-Hyeuk; Shin, Na-Rae; Shin, In-Sik; Kim, Yun-Bae; Kim, Jong-Choon
Abstract: Objective: This study investigated the dose–response effects of pine bark extract (PBE, pycnogenol ® ) on oxidative stress-mediated apoptotic changes induced by cisplatin (Csp) in rats. Materials and methods: The ameliorating potential of PBE was evaluated after orally administering PBE at doses of 10 or 20 mg/kg for 10 days. Acute kidney injury was induced by a single intraperitoneal injection of Csp at 7 mg/kg on test day 5. Results: Csp treatment caused acute kidney injury manifested by elevated levels of serum blood urea nitrogen (BUN) and creatinine (CRE) with corresponding histopathological changes, including degeneration of tubular epithelial cells, hyaline casts in the tubular lumen, and inflammatory cell infiltration (interstitial nephritis). Csp also induced significant apoptotic changes in renal tubular cells. In addition, Csp treatment induced high levels of oxidative stress, as evidenced by an increased level of malondialdehyde, depletion of the reduced glutathione (GSH) content, and decreased activities of glutathione S -transferase, superoxide dismutase, and catalase in kidney tissues. On the contrary, PBE treatment lowered BUN and CRE levels and effectively attenuated histopathological alterations and apoptotic changes induced by Csp. Additionally, treatment with PBE suppressed lipid peroxidation, prevented depletion of GSH, and enhanced activities of the antioxidant enzymes in kidney tissue. Conclusions: These results indicate that PBE has a cytoprotective effect against oxidative stress-mediated apoptotic changes caused by Csp in the rat kidney, which may be attributed to both increase of antioxidant enzyme activities and inhibition of lipid peroxidation.